Klimaethik - Klimapolitik - Klimasoziologie Zur Theorie der sozialen Klimakatastrophe - Günther, Florian C. (Wissenschaftliche Buchgesellschaft (wbg), 2021)
What is meant by the social climate catastrophe? What changes does climate change bring in relation to people and their livelihoods? In this volume, Florian Günther discusses the consequences of climate change and how they relate to social circumstances, deficiencies in development and international climate policy.